Long term complications associated with the ureteric stump in patients with double collecting system who underwent upper pole heminephrectomy - Soisrithong, Chaichant; Ratanapornsompong, Wattanachai; Sirisreetreerux, Pokket; Viseshsindh, Wit (Insight Urology, 2022)
Objective: To assess the long-term ureteric-stump outcomes and complications among patients who had undergone upper-pole heminephrectomies of double collecting systems. Materials and Methods: The medical records of patients who had undergone upper-pole heminephrectomies for non-functioning upper moiety between January 2007 and December 2018 were retrospectively reviewed. Data regarding clinical presentations, age during surgery, operative details, and complications were recorded. Results: Ten patients were included in the study, nine were children and one was an adult. Double collecting systems with ureteroceles were found in four patients, ectopic ureters being found in six. Nine patients had undergone open heminephrectomies, whereas one patient had undergone robot-assisted surgery. Median age at heminephrectomy was one year old (range: 0.58 to 74 years). Median follow-up time was 81.1 months (range: 40.6 to 140.1 months). Median length of hospital stay was seven days (range: 5 to 22 days). Three patients (30%) had stump complications, including stump abscess in one patient, persistent vaginal discharge in another, and a prolapsed ureterocele in the third. Additional interventions were required in two patients, comprising percutaneous drainage of a stump abscess and the excision of a prolapsed ureterocele. Conclusions: Our study found three-cases of long-term complications, with only a single patient requiring distal ureteric stump excision. These findings were similar to another study which also showed that the majority of patients did not require stump excision. Other complications were minor and could be treated by local anesthetic intervention for stump abscess and oral antibiotic for UTI. Therefore, upper pole heminephrectomy with subtotal ureterectomy was the appropriate option for in-patients with double collecting system and non-functioning upper moiety.